Analysis of actuarial experience and acceptance of individual life insurance: A case study in the Iraqi General Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research seeks through the adoption of two basic variables, where he considered the actuarial experience as an independent variable, while the process of accepting the risk and dimensions related to it is a dependent variable, the research was adopted to present the data achieved by the company during the life insurance business during the adoption of actuarial experience at the beginning of its work where Adoption of the historical method in the analysis of those data to prove the researcher's opinion, through the analysis of data (5 years) for the first period, which extends between (1975-1979), the period during which the company adopted the actuarial experience at the time, also taken data for the same dimensions related to the process of acceptance etc. During the period and analysis for the second period, it is also (5 years) related to the second period between the years (2013-2017) in which the company did not adopt the actuarial experience in its business, where the level of decline in the acceptance of individual life insurance policies despite the progress In the size of the population and technological development and health improvement, living, cultural and other, which is supposed to contribute to raise the level of acceptance of insurance policies individual life, and when studying and analysis of the admissions processes for the two periods above and the resulting indicators have been concluded that the lack of actuarial experience in (practical Normal admission, unusual admission, admission to or without medical examination, admission by age group, number of documents admitted from the total number of applications received to the company, required insurance period, etc.) have a significant impact on individual life insurance activity. The study recommended to know the reason for the neglect of the role of actuarial experience in the work of the Iraqi General Insurance Company, in addition to the need to prepare and prepare the actuaries to be relied upon in the future, as well as to be acquainted with the work of international insurance companies that depend on the actuarial experience, as well as work to increase The Awareness about the actuarial profession among the employees of the company, and make it an essential part of the organizational structure, with a focus on the Iraqi Insurance Bureau to take its role in this area, and the preparation of actuarial reports and tariffs in line with the development in society.